2006
DOI: 10.1111/j.1439-0507.2006.01187.x
|View full text |Cite
|
Sign up to set email alerts
|

Nosocomial bloodstream infections associated with Candida species in a Turkish University Hospital

Abstract: In recent years, a progressive increase in the frequency of nosocomial candidaemia has been observed, especially among the critically ill or immunocompromised patients. The aim of this study was to evaluate the trend in incidence of candidaemia together with potential risk factors in an 850-bed Turkish Tertiary Care Hospital in a 4-year period. A total of 104 candidaemia episodes were identified in 104 patients. The overall incidence was 0.56 per 1000 hospital admissions and the increase in incidence of candid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
24
2
7

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 18 publications
5
24
2
7
Order By: Relevance
“…In addition, C. parapsilosis has been found to be associated with the use of central venous catheters and total parenteral nutrition [5]. We did not find any difference in the prevalences of C. albicans and C. parapsilosis among risk factors such as the use of central venous catheters and total parenteral nutrition.…”
Section: Discussionmentioning
confidence: 34%
See 2 more Smart Citations
“…In addition, C. parapsilosis has been found to be associated with the use of central venous catheters and total parenteral nutrition [5]. We did not find any difference in the prevalences of C. albicans and C. parapsilosis among risk factors such as the use of central venous catheters and total parenteral nutrition.…”
Section: Discussionmentioning
confidence: 34%
“…Although there have been numerous studies of candidemia in adults [2,[5][6][7][8]] data on pediatric populations [9][10][11][12] are still limited. The aim of this study was to compare the etiology and risk factors of nosocomial candidemia among pediatric and adult patients at a university hospital in 2007-2009.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ülkemizde yapılan çeşitli çalışmalarda da kan kültürlerinden en sık izole edilen Candida türü C.albicans olarak bildirilmiştir. Bu çalışmalardan bazılarında ikinci sıklıkta izole edilen tür C. parapsilosis (4,5,12,13), bazılarında ise C. tropicalis olarak bildirilmiştir (14,15). Fungal kan dolaşımı infeksiyon etkenleri arasında en sık tespit edilen tür C. albicans olmakla birlikte, son yıllarda albicans…”
Section: Discussionunclassified
“…In a study from our country, C. tropicalis was reported as the second most frequent agent [18]. Between 2000 and 2003, C. albicans (57.7%), C. tropicalis (20.2%), C. parapsilosis (12.5%), and C. glabrata (3.8%) were reported to take the first four ranks among Candida infections at the Dokuz Eylül University School of Medicine [19]. In our study, we have identified the Candida species as C. albicans (52.4%), C. parapsilosis (16.7%), C. glabrata (9.5%), C. tropicalis (7.1%), and C. krusei (4.8%), while 7.1% were non-typed non-albicans Candida species.…”
Section: Discussionmentioning
confidence: 99%